Panamarenko Universum - Willemse, Hans ca. 20. Jh; Miziano, Viktor 1957-; Kreuger, Anders 1965-; De Baere, Bart; Heylen, Philip; Wauters, Stefaan (Ludion - M HKA, 2014)
Panamarenkos assemblages of flying machines, autos and vessels are objects designed to make adventure a reality, not intended as a quick escape from reality. One of the most original contemporary Belgian artists, he is an innovator in all respects. Although his works appeal to the imagination of the beholder, they are often underpinned by scientific calculations. Published on the occasion of an exhibition at the Museum of Modern Art in Antwerp, this book offers a comprehensive and inspired look at Panamarenkos fanciful universe. Exhibition: Museum HKA, Antwerp, Belgium (03.10.2014-22.02.2015)